Lamination of CuCrO2 thin films to poly methyl methacrylate substrate with boron nitride demolding layer. (November 2018) - Lin, Yi-Han; Chiu, Te-Wei; Park, Joon-Hyeong
Abstract: CuCrO2 thin films were prepared on flexible plastic substrate by heat transfer process. Boron nitride (BN) and electrospun CuCrO2 layers were deposited on silicon substrate and used as a demolding layer. Then the CuCrO2 thin film was deposited on the demolding layer by chemical solution deposition and heat treated to form a CuCrO2 /CuCrO2 fiber/BN/Si structure. The CuCrO2 thin film was transferred from the Si substrate to a poly methyl methacrylate (PMMA) substrate. The CuCrO2 /PMMA was characterized by X-ray diffraction and scanning electron microscopy. The resistivity of the CuCrO2 thin films laminated on PMMA substrate was 145 Ω cm, and the transmittance was about 67% in the visible region.